Reframing Catholic and Islamic political theologies: the human good as a basis for public civility - Park, RS (2014)
With the rise of religious plurality and the global public resurgence of religion, deep social unrest and even fatal violence have resulted in a compelling need for plural societies to construct a framework of ‘public civility’. Recently, secularist frameworks such as multiculturalism and legal pluralism have been put forward. Yet, insofar as these approaches are considered non-moral, they are relativistic, and thereby lack the resources needed to ground a universal public civility. Also, approaches to building a ‘just society’ within both Catholic social thought and Islamic jurisprudence have been made specifically on the basis of ‘the common good’. The problem with these approaches is that the so-called ‘common good’ is internally defined such that the ‘good’ is ineluctably uncommon. A more promising basis on which to construct a universal framework of public civility is found in the classical notion of ‘the human good’. The argument proceeds in three main stages: (1) a critical assessment of ideological and sociological forces which have resulted in the fragmentation of modern society and the decline of public life; (2) a delineation of ‘the human good’ on the basis of which I construct a framework of public civility between Catholic and Islamic traditions; and (3) an illustration of the proposed framework in Mindanao, Philippines which represents one of the longest standing internal conflicts in history. The main contention is that Catholic and Islamic political theologies enhance the construction of public civility when reframed in terms of ‘the human good’ in contrast to ‘the common good’. In support of this thesis, I explore the Catholic doctrine of the imago dei and the Islamic notion of fiṭra as prospective conceptual counterparts to the idea of ‘the human good’. I conclude by analyzing the cosmopolitan scope of a framework of public civility as based on ‘the human good’.